Seroprevalence of anti-SARS-CoV-2 antibodies and risk of viral exposure among healthcare workers in the South Kivu province, eastern Democratic Republic of the Congo: a cross-sectional study - Denis Mukwege; Andreas Kalk; Tim Eckmanns; Andreas Nitsche; Fabian H Leendertz; Tshass B Chasinga; Jean-Paul Buhendwa Cikwanine; Sarah Kribi; Jonathan Tunangoya Yoyu; Natalie Hofmann; Marica Grossegesse; Sara Tomczyk; et al. (BMJ Open)
Objectives Healthcare workers (HCWs) are on the frontline of combating COVID-19, hence are at elevated risk of contracting an infection with SARS-CoV-2. The present study aims to measure the impact of SARS-CoV-2 on HCWs in central sub-Saharan Africa.Setting A cross-sectional serological study was conducted at six urban and five rural hospitals during the first pandemic wave in the South Kivu province, Democratic Republic of the Congo (DRC).Participants Serum specimens from 1029 HCWs employed during the first pandemic wave were collected between August and October 2020, and data on demographics and work-related factors were recorded during structured interviews.Primary and secondary outcome measures The presence of IgG antibodies against SARS-CoV-2 was examined by ELISA. Positive specimens were further tested using a micro-neutralisation assay. Factors driving SARS-CoV-2 seropositivity were assessed by multivariable analysis.Results Overall SARS-CoV-2 seroprevalence was high among HCWs (33.1%), and significantly higher in urban (41.5%) compared with rural (19.8%) hospitals. Having had presented with COVID-19-like symptoms before was a strong predictor of seropositivity (31.5%). Personal protective equipment (PPE, 88.1% and 11.9%) and alcohol-based hand sanitizer (71.1% and 28.9%) were more often available, and hand hygiene was more often reported after patient contact (63.0% and 37.0%) in urban compared with rural hospitals, respectively. This may suggest that higher exposure during non-work times in high incidence urban areas counteracts higher work protection levels of HCWs.Conclusions High SARS-CoV-2 seropositivity indicates widespread transmission of the virus in this region of DRC. Given the absence of publicly reported cases during the same time period at the rural sites, serological studies are very relevant in revealing infection dynamics especially in regions with low diagnostic capacities. This, and discrepancies in the application of PPE between urban and rural sites, should be considered in future pandemic response programmes.